Manipulation of HSP70-SOD1 Expression Modulates SH-SY5Y Differentiation and Susceptibility to Oxidative Stress-Dependent Cell Damage: Involvement in Oxotremorine-M-Mediated Neuroprotective Effects - Miriana Scordino; Monica Frinchi; Giulia Urone; Domenico Nuzzo; Giuseppa Mudò; Valentina Di Liberto (MDPI AG, 2023)
The differentiation of neural progenitors is a complex process that integrates different signals to drive transcriptional changes, which mediate metabolic, electrophysiological, and morphological cellular specializations. Understanding these adjustments is essential within the framework of stem cell and cancer research and therapy. Human neuroblastoma SH-SY5Y cells, widely used in neurobiology research, can be differentiated into neuronal-like cells through serum deprivation and retinoic acid (RA) supplementation. In our study, we observed that the differentiation process triggers the expression of Heat Shock Protein 70 (HSP70). Notably, inhibition of HSP70 expression by KNK437 causes a dramatic increase in cell death. While undifferentiated SH-SY5Y cells show a dose-dependent decrease in cell survival following exposure to hydrogen peroxide (H2O2), differentiated cells become resistant to H2O2-induced cell death. Interestingly, the differentiation process enhances the expression of SOD1 protein, and inhibition of HSP70 expression counteracts this effect and increases the susceptibility of differentiated cells to H2O2-induced cell death, suggesting that the cascade HSP70-SOD1 is involved in promoting survival against oxidative stress-dependent damage. Treatment of differentiated SH-SY5Y cells with Oxotremorine-M (Oxo), a muscarinic acetylcholine receptor agonist, enhances the expression of HSP70 and SOD1 and counteracts tert-Butyl hydroperoxide-induced cell death and reactive oxygen species (ROS) generation. It is worth noting that co-treatment with KNK437 reduces SOD1 expression and Oxo-induced protection against oxidative stress damage, suggesting the involvement of HSP70/SOD1 signaling in this beneficial effect. In conclusion, our findings demonstrate that manipulation of the HSP70 signal modulates SH-SY5Y differentiation and susceptibility to oxidative stress-dependent cell death and unravels novel mechanisms involved in Oxo neuroprotective functions. Altogether these data provide novel insights into the mechanisms underlying neuronal differentiation and preservation under stress conditions.